The Importance of AI in Teaching English Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the growing role of Artificial Intelligence (AI) in education, highlighting its potential to personalize learning, streamline administrative tasks, and enhance student engagement. AI enables tailored educational experiences by adapting to individual learning needs and providing real-time feedback.. Overall, AI can significantly improve education when integrated responsibly alongside traditional teaching methods.